THE ROLE OF AGE / RAGE IN THE PATHOPHYSIOLOGY OF THE DIABETES-PERIODONTITIS RELATIONSHIP - Diana-Maria Anton; Maria-Alexandra Martu; Irina-Georgeta Sufaru; Liliana Pasarin; Ionut Luchian; Mihaela Maris; Monica Scutariu; Ioana Martu (Romanian Dental Association for Education, 2020)
RAGE has historically been studied in periodontitis associated with diabetes. Activation of RAGE generates pro-inflammatory signals through its interaction with glycated molecules present in the serum and tissues of diabetic patients. This process is described as the AGE / RAGE axis. A body of evidence tends to show the involvement of this same receptor in the pathophysiology of periodontitis alone (not associated with diabetes). At the tissue level, RAGE is overexpressed in sites affected by periodontitis concomitantly with its AGER1 antagonist, limiting its inflammatory action. Finally, the serum concentration of the cleaved soluble forms of RAGE is reduced in periodontal patients and is negatively correlated with the clinical parameters of periodontitis. The pathophysiology of periodontitis seems to have an impact on the concentration of this antioxidant biomarker. The variation in the serum concentration of RAGE is associated with many systemic pathologies.